2003
DOI: 10.1144/gsl.sp.2003.219.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic history of the back-arc region of the Izu-Bonin (Ogasawara) arc

Abstract: The laser-heating 40Ar/39Ar dating method was applied to volcanic rocks systematically collected from the back-arc region of the central part of the Izu-Bonin arc. Dating results combined with whole-rock chemistry and other geological information reveal the volcanic history of the back-arc region of the Izu-Bonin arc. In the back-arc seamount chains area, andesitic-basaltic volcanism initiated at c. 17 Ma, slightly before the Shikoku Basin ceased spreading, and continued until c. 3 Ma. Relatively old volcanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(120 citation statements)
references
References 30 publications
7
112
0
1
Order By: Relevance
“…NE-SW trending faults cut the northern part of the Sandwich plate (Fig. 3), which are possibly a result of plate boundary forces and the seamount trends may be controlled by the same stresses.The cross-cutting South Sandwich seamount chains are comparable to en echelon seamount chains between 30° and 32.5°N in the Izu-Bonin arc which extend similar distances (some 40-70 km from the intra-arc rift zone) toward the back-arc basin, intersect the arc trend at similar angles (approximately 70°), and have similar volumes (typically 50-100 km 3 for individual seamounts) (Ishizuka et al, 2003;Machida et al, 2008). Seamount chains with similar dimensions and cross-cutting relationships also extend from the volcanic arc into the rear-arc in the Northern Seamount Province of the Mariana arc (Stern et al, 1993).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…NE-SW trending faults cut the northern part of the Sandwich plate (Fig. 3), which are possibly a result of plate boundary forces and the seamount trends may be controlled by the same stresses.The cross-cutting South Sandwich seamount chains are comparable to en echelon seamount chains between 30° and 32.5°N in the Izu-Bonin arc which extend similar distances (some 40-70 km from the intra-arc rift zone) toward the back-arc basin, intersect the arc trend at similar angles (approximately 70°), and have similar volumes (typically 50-100 km 3 for individual seamounts) (Ishizuka et al, 2003;Machida et al, 2008). Seamount chains with similar dimensions and cross-cutting relationships also extend from the volcanic arc into the rear-arc in the Northern Seamount Province of the Mariana arc (Stern et al, 1993).…”
mentioning
confidence: 78%
“…Seamount chains with similar dimensions and cross-cutting relationships also extend from the volcanic arc into the rear-arc in the Northern Seamount Province of the Mariana arc (Stern et al, 1993). Ar-Ar dating of the Izu-Bonin back-arc seamounts indicates that they are locally as old as 17 Ma but mostly erupted during the period 10-3 Ma with age progression of magmatism along the chains toward the volcanic front (Ishizuka et al, 2003). Such long-lived magmatism along narrow loci suggests lithospheric structural control.…”
Section: Seamount Cross-chains and Rear-arc Volcanismmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the interpretation and characteristics of each unit in the highresolution survey are almost the same as in the earlier pre-site survey, many reflectors can be seen within each unit. Ishizuka et al (2003) reported 40 Ar-39 Ar ages of dredge samples from volcanic seamounts near the drilling site U1437 and the seismic lines (Figure 2). The samples from the top of these seamounts have different ages, reflecting the date of igneous activity along the seamount chain.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Based on analysis of magnetic and gravity anomalies, Yamazaki and Yuasa (1998) proposed that rifting had occurred in the western half of the IzuOgasawara rear arc during the middle Miocene, immediately after spreading ended in the Shikoku Basin. On the other hand, Ishizuka et al (2003) focused on the rear-arc seamount chains, and revealed the temporal variation of the volcanism and the subsequent rifting, based on eruption ages from dredged samples. They dredged rocks with lithologies ranging from basalts to dacites and ages from 17 to 3 Ma from many of the seamounts around the Izu-Ogasawara rear arc.…”
Section: Introductionmentioning
confidence: 99%